750. Respiratory Virus Infections and Airflow Obstruction After Allogeneic Hematopoietic Cell Transplantation. (26th November 2018) - Boeckh, Michael; Campbell, Angela P; Cheng, Guang-Shing; Xie, Hu; Kuypers, Jane; Callais, Cheryl; Waghmare, Alpana; Stevens-Ayers, Terry; Jerome, Keith; Chien, Jason; Leisenring, Wendy; Englund, Janet
Abstract: Background: Respiratory viruses are readily detectable in hematopoietic cell transplant (HCT) recipients in the molecular diagnostic era. The association of respiratory virus infections with acute and chronic airflow obstruction (AFO) is poorly defined. Methods: HCT recipients were prospectively followed with weekly handheld spirometry and symptom questionnaires through 1 year after HCT. Weekly multiplex PCR testing for 11 respiratory viruses was performed through day 100 post-HCT and every 3 months and with respiratory symptoms thereafter. Standard pulmonary function testing occurred at recommended intervals. Cox proportional hazard models were used to correlate longitudinal symptomatic respiratory tract viral infections with AFO phenotypes, defined as 2- or 4-week decline (↓) of 1 second forced expiratory volume (FEV1) >10% by handheld spirometry; late AFO (FEV1/forced vital capacity [FVC] < lower limit normal predicted and FEV1 decline >10% from baseline at 3 years; or bronchiolitis obliterans syndrome (BOS; FEV1 <75%, FEV1/FVC < 0.7, and FEV1 ↓ >10% from baseline) by 3 years after HCT; late AFO and BOS were assessed by standard pulmonary function testing. Results: Overall, 7, 091 PCR tests were performed in 471 patients; 70% of patients had ≥1 respiratory virus detected. Among 437 patients who survived >4 weeks, decline of FEV-1 for 2 or 4 weeks, late AFO or BOS occurred in 11.9%, 7.1%, 15.6%, and 3.9%, respectively. In adjusted Cox models, human metapneumovirus (HMPV), influenza virus A/B, and parainfluenza virus 1–4 (PIV) upper tract infections (URI) were associated with 2 and 4 weeks FEV-1 decline (Figure 1). Late AFO and BOS were only significantly associated with RSV- or HMPV-related URI (Figure 2). Lower respiratory disease (LRD) due to HMPV (adjusted HR 11.1, P = 0.02) was associated with a 2- and 4-week FEV-1 decline. Conclusion: Development of AFO after HCT is common. Respiratory viruses are significantly associated with both short-term airflow decline and long-term airflow obstruction. Interventional strategies that target multiple viruses are warranted. Disclosures: M. Boeckh, Gilead Sciences: Consultant, Grant Investigator and Investigator, Clinical trial support, Consulting fee and Research grant. Asun Biopharma: Consultant, Grant Investigator and Investigator, Clinical trial support, Consulting fee and Research grant. Humabs: Consultant, Consulting fee. Aviragen: Consultant and Grant Investigator, Consulting fee and Research grant. Chimerix Inc.: Consultant, Grant Investigator and Investigator, Clinical trial support, Consulting fee and Research grant. Ablynx: Consultant and Investigator, Clinical trial support and Consulting fee. GSK: Investigator, Clinical trial support. A. Waghmare, Ablynx: Investigator, Research support. Vicol: Investigator, Research support. J. Chien, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. J. Englund, Gilead: Consultant and Investigator, Consulting fee and Research support. Novavax: Investigator, Research support. GlaxoSmithKline: Investigator, Research support. Alios: Investigator, Research support. MedImmune: Investigator, Research support.